Papel do novo derivado N Acilidrazónico inibidor de histona desacetilases 6/8 sobre células de Melanoma Humano - Caiman Peñarete, Leydy Alexandra (2018)
Melanoma is one of the cancers with the highest mortality rate. This tumor has had an important increase in the last 50 years, mainly in the clear skin population and in regions of low latitude. In Brazil, the National Cancer Institute estimates for the biennium 2018-2019, 2920 new cases of melanoma among men and 3340 in women, with a mortality higher than 80 percent. The development of resistance to traditional treatments and serious adverse effects in patients leads to the need to develop alternative treatments. One of the most commonly used current treatments is histone deacetylase inhibitors, but with very severe adverse effects for patients. Histone deacetylases (HDACs) are epigenetic enzymes that represent research targets for the development of therapies for the treatment of solid tumors. Recently, new inhibitors HDACs have been synthesized in search of greater specificity and catalytic activity, in addition to greater therapeutic efficiency. In the present study, we investigated the in vitro effects of a new class of Nacylhydrazone (NAH) derivatives that act as double acting inhibitors of HDACs 6 and 8 in cells derived from metastatic melanoma. Thus, we found that compound 3C reduces cell viability of WM-1366 and HT-144 melanoma cells, decreasing clonogenic capacity, more strongly in WM- 1366 cells, inducing cell cycle arrest in G2 / M phases in both strains, in addition to increased transcription of the p21 gene and reduced expression of Cyclin B1, PLK1, AURKA and AURKB. These results suggest that the 3C molecule is a promising therapeutic alternative as an inhibitor of HDAC 6/8 in the treatment of human melanoma.